Charm fragmentation fractions and $$\mathbf {c\overline{c}}$$ c c ¯ cross section in p–Pb collisions at $$\mathbf {\sqrt{s _{NN}}=5.02 TeV}$$ s NN = 5.02 TeV - ALICE Collaboration (European Physical Journal C: Particles and Fields)
Abstract The total charm-quark production cross section per unit of rapidity $$\textrm{d}\sigma ({{\textrm{c}}\overline{\textrm{c}}})/\textrm{d}y$$ d σ ( c c ¯ ) / d y , and the fragmentation fractions of charm quarks to different charm-hadron species $$f(\textrm{c}\rightarrow {\textrm{h}}_{\textrm{c}})$$ f ( c → h c ) , are measured for the first time in p–Pb collisions at $$\sqrt{s_\textrm{NN}} = 5.02~\text {Te}\hspace{-1.00006pt}\textrm{V} $$ s NN = 5.02 Te V at midrapidity ( $$-0.96<y<0.04$$ - 0.96 < y < 0.04 in the centre-of-mass frame) using data collected by ALICE at the CERN LHC. The results are obtained based on all the available measurements of prompt production of ground-state charm-hadron species: $$\textrm{D}^{0}$$ D 0 , $$\textrm{D}^{+}$$ D + , $$\textrm{D}_\textrm{s}^{+}$$ D s + , and $$\mathrm {J/\psi }$$ J / ψ mesons, and $$\Lambda _\textrm{c}^{+}$$ Λ c + and $$\Xi _\textrm{c}^{0}$$ Ξ c 0 baryons. The resulting cross section is $$ \textrm{d}\sigma ({{\textrm{c}}\overline{\textrm{c}}})/\textrm{d}y =219.6 \pm 6.3\;(\mathrm {stat.}) {\;}_{-11.8}^{+10.5}\;(\mathrm {syst.}) {\;}_{-2.9}^{+8.3}\;(\mathrm {extr.})\pm 5.4\;(\textrm{BR})\pm 4.6\;(\mathrm {lumi.}) \pm 19.5\;(\text {rapidity shape})+15.0\;(\Omega _\textrm{c}^{0})\;\textrm{mb} $$ d σ ( c c ¯ ) / d y = 219.6 ± 6.3 ( stat . ) - 11.8 + 10.5 ( syst . ) - 2.9 + 8.3 ( extr . ) ± 5.4 ( BR ) ± 4.6 ( lumi . ) ± 19.5 ( rapidity shape ) + 15.0 ( Ω c 0 ) mb , which is consistent with a binary scaling of pQCD calculations from pp collisions. The measured fragmentation fractions are compatible with those measured in pp collisions at $$\sqrt{s} = 5.02$$ s = 5.02 and 13 TeV, showing an increase in the relative production rates of charm baryons with respect to charm mesons in pp and p–Pb collisions compared with $$\mathrm {e^{+}e^{-}}$$ e + e - and $$\mathrm {e^{-}p}$$ e - p collisions. The $$p_\textrm{T}$$ p T -integrated nuclear modification factor of charm quarks, $$R_\textrm{pPb}({\textrm{c}}\overline{\textrm{c}})= 0.91 \pm 0.04\;\mathrm{(stat.)} ^{+0.08}_{-0.09}\;\mathrm{(syst.)} ^{+0.05}_{-0.03}\;\mathrm{(extr.)} \pm 0.03\;\mathrm{(lumi.)}$$ R pPb ( c c ¯ ) = 0.91 ± 0.04 ( stat . ) - 0.09 + 0.08 ( syst . ) - 0.03 + 0.05 ( extr . ) ± 0.03 ( lumi . ) , is found to be consistent with unity and with theoretical predictions including nuclear modifications of the parton distribution functions.